Pemanfaatan dan Pelestarian Hutan Mangrove di Desa Koepisino Kecamatan Bonegunu Kabupaten Buton Utara - Yadi, Yadi; Marhadi, Akhmad; Rahman, Abdul (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This research aims to find out and describe the benefits of mangrove forests in Koepisino Village, Bonegunu District, North Buton Regency and the efforts of the community and government in preserving mangrove forests in Koepisino Village, Bonegunu District, North Buton Regency. This research method uses a qualitative descriptive research method. The data collection techniques used in this research are observation, interviews and documentation methods. The theory used is Cultural Ecology Theory by Julian H Steward. The results of this research show that mangrove wood is very useful for the people of Koepisino village, one of which is as a tool for building houses, such as house frames, rafters and boards, apart from being useful for building houses, it is also used as firewood, slanted poles and para-para for drying jelly. . The Koepisino Village community also conserves mangrove forests together with the local government, the community looks for mangrove wood seeds, plants and controls the growth of the mangrove plants that have been planted, while the government only provides a budget for preservation and supervises the community who carry out the planting.